Religious Organizations in the Practice of Total People’s Defense: Muhammadiyah’s Strategy in Responding to the COVID-19 Pandemic - Ul Haq, Fajar Riza (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2025)
The COVID-19 pandemic has transformed Indonesia’s national defense paradigm from a militaristic orientation to a model of total social defense based on community participation. This study aims to analyze how Muhammadiyah, as a religious organization in Indonesia, implemented the practice of Total People’s Defense (Sistem Pertahanan Semesta/SISHANTA) through civil society–based strategies during the pandemic crisis. Employing a qualitative case study approach, this research explores Muhammadiyah’s strategies and resource mobilization patterns through the Muhammadiyah COVID-19 Command Center (MCCC). Data were collected through document analysis, in-depth interviews, and field observations in three key regions: Yogyakarta, Jakarta, and West Sumatra Findings show that Muhammadiyah operationalized three key pillars of defense: health (defense of life), education (defense of knowledge), and economy (defense of welfare). These dimensions illustrate a model of civil defense that integrates faith, science, and humanitarian action to strengthen national resilience. Muhammadiyah’s experience illustrates that total defense can be realized through moral conviction, social solidarity, and institutional collaboration. Faith-based organizations serve not only as humanitarian agents but also as partners in safeguarding national stability and human security. The study suggests the need for stronger integration of civil and faith-based organizations into Indonesia’s national defense policy and the inclusion of civic and humanitarian values in educational curricula to cultivate resilience. This study focuses on a single case Muhammadiyah’s response in three regions during the 2020–2022 pandemic thus limiting generalization. Future research should adopt comparative approaches to explore broader models of civil-based defense in Indonesia.